Factors Affecting Consumer Demand for Cayenne Pepper in Denpasar City, Bali Province - YANTI, NI MADE SRI WEGA; SUSRUSA, KETUT BUDI; LISTIADEWI, IDA AYU (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.8, No.2, April 2019, 2019)
Factors Affecting Consumer Demand for Cayenne Pepper in Denpasar City, Bali Province Cayenne pepper is one of the national leading commodities that is needed by the community. Denpasar City, which has a high population density and per capita food expenditure, is a potential market for cayenne pepper production centers in Bali Province. Consumer demand for cayenne pepper is sometimes uncertain due to the influence of various factors. This study aims to analyze the factors that influence consumer demand for cayenne pepper and analyze its demand elasticity in Denpasar City, Bali Province.This research was carried out in Badung Market, Kreneng Market, Ketapian Market, and Sanglah Marketwhich were determined intentionally. Sampling used accidental sampling technique. The number of samples was determined by quota sampling as many as 50 respondents. This study used the Cobb-Douglas request function which is transformed into multiple linear forms of natural logarithms (ln).The results showed that the factors that influence consumer demand for cayenne pepper in Denpasar City, Bali Province were the number of family members and tastes. Price elasticity at D = 0 (not interested in cayenne pepper) and D = 1 (interested in cayenne pepper) shows that the demand for cayenne pepper is perfectly inelastic. Cross elasticity at D = 0 (not interested in cayenne pepper) and D = 1 (interested in cayenne pepper) showed that large red chilies, tomatoes, and shallots are items that were not related to cayenne pepper. Income elasticity at D = 0 (not interested in cayenne pepper) and D = 1 (interested in cayenne pepper) indicates that the demand for cayenne pepper was inelastic to income.